(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
From an ethical and legal point of view, the assent of the minor to participate in a medical study is a subject of great importance. There is still a debate about the requirements to consider this assent valid and binding. This review analyses and compares the contents of the assent from the points of view of the legislation and the scientific literature.